Split-incentives in energy efficiency investments? Evidence from rental housing - Puja Singhal; Stephan Sommer; Kathrin Kaestner; Michael Pahle (RWI - Leibniz-Institut für Wirtschaftsforschung, 2023)
Rental housing where tenants are responsible for their own energy bills but landlords are responsible for energy retrofits may pose a particular challenge in achieving optimal rates of investments in energy efficiency. In this paper, we investigate the severity of this split-incentive problem in thermal efficiency investments in the German housing market, where the share of renters is among the highest in the European Union and the majority of rented apartments is owned by private individuals. Using data on energy performance scores from Germany's largest online housing market platform between 2019 and 2021, we find economically small differences in the energy efficiency levels between apartments that are offered for sale for own use compared to those that are rented out on the housing market. These findings suggest that there may not be a critical energy efficiency deficit due to the high share of renters in the multi apartment building sector. – – In Mietwohnungen, bei denen Mietende selbst für ihre Energierechnungen verantwortlich sind, Vermietende aber für die für energetische Sanierungen, ist es besonders herausfordernd, optimale Investitionsraten bei der Energieeffizienz zu erreichen. In diesem Papier untersuchen wir das Ausmaß dieses Split-Incentive-Problems bei Investitionen in die thermische Effizienz auf dem deutschen Wohnungsmarkt, wo der Mietanteil zu den höchsten in der Europäischen Union gehört und die Mehrheit der Mietwohnungen von privaten Personen vermietet wird. Auf Grundlage von Daten von Deutschlands größter Online-Wohnungsmarktplattform zur Bewertung der Gesamtenergieeffizienz finden wir ökonomisch geringe Unterschiede in der Energieeffizienz zwischen Wohnungen, die zur Eigennutzung angeboten werden und jenen, die vermietet werden. Diese Ergebnisse legen nahe, dass es möglicherweise kein kritisches Energieeffizienzdefizit im Mehrfamilien-Sektor gibt.
Keywords: Q41; Q50; Q54; 330; Energy efficiency; split-incentives; housing market; owner-renter problem